10 narradores españoles - Beneyto, Antonio ((Libro Amigo ;)
Contiene cuentos o fragmentos de novelas de: Camilo José Cela, Francisco Umbral, Juan Goytisolo, Juan Marsé, Manuel Vázquez Montalbán, Rosa Chacel, Alvaro Cunqueiro, Alfonso Sastre, Ana María Matute y Carlos Edmundo de Ory.